Relatório de estágio curricular no Juízo Central Criminal de Lisboa, - Sebastião, Eugénia de Oliveira Godinho Patriarca (2022)
This report comes from four intensive months of internship which followed the daily operation of a collective court in the Lisbon Central Criminal Court, as well as all the remaining collaborators in the exercise of jurisdictional activity. As work of a practical nature, it is carried out a contextualization of the court, of the developed activities during the internship and, also, of the preponderant criminality. As juridical research work, this report deepens the issue of the probative value of the statements of a co-accused to the detriment of another co-accused. It goes through a historical evolution regarding this means of proof, followed by an assessment of its criteria and valuation limits, as well as a brief approach of them in the scope of the European Court of Human Rights and the European Convention on Human Rights. Following the accused's behaviour in criminal proceedings, the issue of rewarded collaboration is introduced. Initially, Law No. 12.850/2013 in force in Brazil is analyzed and, later, the configuration of this institute is exposed in the Portuguese legal system. The figure of the repentant/collaborating accused is described, observing the value of his statements. Finally, the possibility of implementing Brazilian law in Portugal is studied, confronted with current procedural principles. In summary, the present report intends to demonstrate, based on the analysis recorded during the internship, issues that have been raised within the scope of the accused’s statements and, to what extent, their credibility and valuation can occur, determining since a possible benefit or procedural advantage until the exemption or mitigation of the penalty applicable to the crimes committed.